(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The global spread of digital technologies in the 21st century has also had an impact on the education system, including the methods of teaching fine arts in schools. Some countries with the most advanced education systems in the world have begun to use digital technologies not only as a teaching tool, but also as a key skill of the future. The education system in Uzbekistan has also been developing steadily in recent years, and in this process, the adoption of world best practices is of great importance. In this article, we studied the experience of using digital technologies in the teaching of fine arts in two leading countries, Finland and South Korea, in order to increase the effectiveness of art education in schools of Uzbekistan. The results have shown that the integration of digital technologies into art education leads to the improvement of students’ readiness for the future and helps them to explore a new world of art as well as save the traditional approaches.